Assessment of Corrosion Education - National Research Council (The National Academies Press, 2009)
The threat from the degradation of materials in the engineered products that drive our economy, keep our citizenry healthy, and keep us safe from terrorism and belligerent threats has been well documented over the years. And yet little effort appears to have been made to apply the nation's engineering community to developing a better understanding of corrosion and the mitigation of its effects. The engineering workforce must have a solid understanding of the physical and chemical bases of corrosion, as well as an understanding of the engineering issues surrounding corrosion and corrosion abatement. Nonetheless, corrosion engineering is not a required course in the curriculum of most bachelor degree programs in MSE and related engineering fields, and in many programs, the subject is not even available. As a result, most bachelor-level graduates of materials- and design-related programs have an inadequate background in corrosion engineering principles and practices. To combat this problem, the book makes a number of short- and long-term recommendations to industry and government agencies, educational institutions, and communities to increase education and awareness, and ultimately give the incoming workforce the knowledge they need.
Keywords: Engineering and Technology

Review of the Bureau of Reclamation's Corrosion Prevention Standards for Ductile Iron Pipe - National Research Council (The National Academies Press, 2009)
Ductile iron pipe (DIP) was introduced about 50 years ago as a more economical and better-performing product for water transmission and distribution. As with iron or steel pipes, DIP is subject to corrosion, the rate of which depends on the environment in which the pipe is placed. Corrosion mitigation protocols are employed to slow the corrosion process to an acceptable rate for the application. When to use corrosion mitigation systems, and which system, depends on the corrosivity of the soils in which the pipeline is buried. The Bureau of Reclamation's specification for DIP in highly corrosive soil has been contested by some as an overly stringent requirement, necessitating the pipe to be modified from its as-manufactured state and thereby adding unnecessary cost to a pipeline system. This book evaluates the specifications in question and presents findings and recommendations. Specifically, the authoring committee answers the following questions:
Keywords: Engineering and Technology; Transportation and Infrastructure

Guidelines for Rail Base Inspection and Rail Condemnation Limits for Corrosion-Induced Material Loss - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2009)
TRB’s Transit Cooperative Research Program (TCRP) Web-Only Document 47: Guidelines for Rail Base Inspection and Rail Condemnation Limits for Corrosion-Induced Material Loss explores the maximum allowable material loss in the rail base as part of an evaluation of the causes and effects of corrosion on rail base.
Keywords: Transportation and Infrastructure

Evaluation of Future Strategic and Energy Efficient Options for the U.S. Capitol Power Plant - National Research Council (The National Academies Press, 2009)
The U.S. Capitol Complex in Washington, D.C., comprises some of the most historic and symbolic buildings in the nation. The steam and chilled water required to heat and cool these buildings and related equipment is generated and distributed by the Capitol Power Plant (CPP) district energy system. Portions of the CPP system are now 50 to 100 years old and require renewal so that reliable utility services can be provided to the U.S. Capitol Complex for the foreseeable future. Evaluation of Future Strategic and Energy Efficient Options for the U.S. Capitol Power Plant provides comments on an interim set of publicly available consultant-generated options for the delivery of utility services to the U.S. Capitol Complex. The report provides recommendations to bring the interim options to completion, including suggestions for additional analyses, so that the CPP can be best positioned to meet the future strategic and energy efficiency requirements of the U.S. Capitol Complex.
Keywords: Energy and Energy Conservation

Frontiers in Crystalline Matter: From Discovery to Technology - National Research Council (The National Academies Press, 2009)
For much of the past 60 years, the U.S. research community dominated the discovery of new crystalline materials and the growth of large single crystals, placing the country at the forefront of fundamental advances in condensed-matter sciences and fueling the development of many of the new technologies at the core of U.S. economic growth. The opportunities offered by future developments in this field remain as promising as the achievements of the past. However, the past 20 years have seen a substantial deterioration in the United States' capability to pursue those opportunities at a time when several European and Asian countries have significantly increased investments in developing their own capacities in these areas. This book seeks both to set out the challenges and opportunities facing those who discover new crystalline materials and grow large crystals and to chart a way for the United States to reinvigorate its efforts and thereby return to a position of leadership in this field.
Keywords: Math, Chemistry, and Physics; Engineering and Technology

2007-2008 Assessment of the Army Research Laboratory - National Research Council (The National Academies Press, 2009)
This volume is the latest in a series of biennial assessments of the scientific and technical quality of the Army Research Laboratory (ARL). The current report summarizes findings for the 2007-2008 period, during which 95 volunteer experts in fields of science and engineering participated in the following activities: visiting ARL annually, receiving formal presentations of technical work, examining facilities, engaging in technical discussions with ARL staff, and reviewing ARL technical materials.
Keywords: Policy for Science and Technology; Conflict and Security Issues

Medical Isotope Production Without Highly Enriched Uranium - National Research Council (The National Academies Press, 2009)
This book is the product of a congressionally mandated study to examine the feasibility of eliminating the use of highly enriched uranium (HEU2) in reactor fuel, reactor targets, and medical isotope production facilities. The book focuses primarily on the use of HEU for the production of the medical isotope molybdenum-99 (Mo-99), whose decay product, technetium-99m3 (Tc-99m), is used in the majority of medical diagnostic imaging procedures in the United States, and secondarily on the use of HEU for research and test reactor fuel. The supply of Mo-99 in the U.S. is likely to be unreliable until newer production sources come online. The reliability of the current supply system is an important medical isotope concern; this book concludes that achieving a cost difference of less than 10 percent in facilities that will need to convert from HEU- to LEU-based Mo-99 production is much less important than is reliability of supply.
Keywords: Environment and Environmental Studies

An Assessment of the SBIR Program at the National Aeronautics and Space Administration - National Research Council (The National Academies Press, 2009)
The Small Business Innovation Research (SBIR) program is one of the largest examples of U.S. public-private partnerships. Founded in 1982, SBIR was designed to encourage small business to develop new processes and products and to provide quality research in support of the many missions of the U.S. government, including health, energy, the environment, and national defense. In response to a request from the U.S. Congress, the National Research Council assessed SBIR as administered by the five federal agencies that together make up 96 percent of program expenditures. This book, one of six in the series, reports on the SBIR program at the National Aeronautics and Space Administration, and finds that the program is making significant progress in achieving the Congressional goals for the program. Keeping in mind NASA's unique mission and the recent significant changes to the program, the committee found the SBIR program to be sound in concept and effective in practice at NASA.. The book recommends programmatic changes that should make the SBIR program even more effective in achieving its legislative goals.
Keywords: Industry and Labor; Space and Aeronautics

A Review of the NIOSH Roadmap for Research on Asbestos Fibers and Other Elongate Mineral Particles - Institute of Medicine; National Research Council (The National Academies Press, 2009)
Although asbestos is no longer mined in the United States, prior and ongoing exposures to asbestos continue to contribute to respiratory diseases, including mesothelioma, lung cancer, and asbestosis. To examine ongoing issues and concerns in this field, the National Institute for Occupational Safety and Health (NIOSH) drafted a research roadmap, Asbestos Fibers and Other Elongated Mineral Particles: State of the Science and Roadmap for Research, that provides an overview of the state of the science and a plan for future research in areas including toxicology, mineralogy, epidemiology, and exposure assessment.
Keywords: Health and Medicine

Evaluating Occupational Health and Safety Research Programs: Framework and Next Steps - Institute of Medicine; National Research Council (The National Academies Press, 2009)
Each year, approximately 5,000 fatal work-related injuries and 4 million non-fatal injuries and illnesses occur in the United States. This number represents both unnecessary human suffering and high economic costs. In order to assist in better evaluating workplace safety and create safer work environments, the Institute of Medicine conducted a series of evaluations of the National Institute for Occupational Safety and Health (NIOSH) research programs, assessing the relevance and impact of NIOSH's work on improving worker safety and health.
Keywords: Industry and Labor; Health and Medicine

A Survey of Attitudes and Actions on Dual Use Research in the Life Sciences: A Collaborative Effort of the National Research Council and the American Association for the Advancement of Science - National Research Council (The National Academies Press, 2009)
The same technologies that fuel scientific advances also pose potential risks—that the knowledge, tools, and techniques gained through legitimate biotechnology research could be misused to create biological weapons or for bioterrorism. This is often called the dual use dilemma of the life sciences. Yet even research with the greatest potential for misuse may offer significant benefits. Determining how to constrain the danger without harming essential scientific research is critical for national security as well as prosperity and well-being. This book discusses a 2007 survey of American Association for the Advancement of Science (AAAS) members in the life sciences about their knowledge of dual use issues and attitudes about their responsibilities to help mitigate the risks of misuse of their research. Overall, the results suggest that there may be considerable support for approaches to oversight that rely on measures that are developed and implemented by the scientific community itself. The responses also suggest that there is a need to clarify the scope of research activities of concern and to provide guidance about what actions scientists can take to reduce the risk that their research will be misused by those with malicious intent.
Keywords: Policy for Science and Technology; Biology and Life Sciences; Conflict and Security Issues

The 2nd International Forum on Biosecurity: Summary of an International Meeting - National Research Council (The National Academies Press, 2009)
The 2nd International Forum on Biosecurity, held in Budapest, Hungary on March 30 - April 2, 2008, represents the efforts of a number of individuals and organizations, over the last five years, to engage the international community of life scientists in addressing how to reduce the risk that the results of their work could be used for hostile purposes by terrorists and states. The participants who gathered in Budapest were already engaged in this challenging task, and, therefore, the focus of the meeting was on what had been accomplished and what challenges remained. There was no attempt to achieve consensus, since there exist real and important differences among those involved concerning the appropriate policies and actions to be undertaken. But there was a serious effort to identify a range of potential next steps, and also an effort to identify opportunities where international scientific organizations could make substantive contributions and offer their advice and expertise to policy discussions. The Forum's presentations, discussions, and results are summarized in this book.
Keywords: Conflict and Security Issues

Advice on the Department of Energy's Cleanup Technology Roadmap: Gaps and Bridges - National Research Council (The National Academies Press, 2009)
Beginning with the Manhattan Project and continuing through the Cold War, the United States government constructed and operated a massive industrial complex to produce and test nuclear weapons and related technologies. When the Cold War ended, most of this complex was shut down permanently or placed on standby, and the United States government began a costly, long-term effort to clean up the materials, wastes, and environmental contamination resulting from its nuclear materials production.
Keywords: Environment and Environmental Studies

Biographical Memoirs: Volume 91 - National Academy of Sciences (The National Academies Press, 2009)
Biographic Memoirs Volume 91 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Internationalization of the Nuclear Fuel Cycle: Goals, Strategies, and Challenges - National Academy of Sciences; National Research Council (The National Academies Press, 2009)
The so-called nuclear renaissance has increased worldwide interest in nuclear power. This potential growth also has increased, in some quarters, concern that nonproliferation considerations are not being given sufficient attention. In particular, since introduction of many new power reactors will lead to requiring increased uranium enrichment services to provide the reactor fuel, the proliferation risk of adding enrichment facilities in countries that do not have them now led to proposals to provide the needed fuel without requiring indigenous enrichment facilities. Similar concerns exist for reprocessing facilities. Internationalization of the Nuclear Fuel Cycle summarizes key issues and analyses of the topic, offers some criteria for evaluating options, and makes findings and recommendations to help the United States, the Russian Federation, and the international community reduce proliferation and other risks, as nuclear power is used more widely. This book is intended for all those who are concerned about the need for assuring fuel for new reactors and at the same time limiting the spread of nuclear weapons. This audience includes the United States and Russia, other nations that currently supply nuclear material and technology, many other countries contemplating starting or growing nuclear power programs, and the international organizations that support the safe, secure functioning of the international nuclear fuel cycle, most prominently the International Atomic Energy Agency.
Keywords: Energy and Energy Conservation; Conflict and Security Issues; Industry and Labor

Future of the Nuclear Security Environment in 2015: Proceedings of a Russian-U.S. Workshop - National Academy of Sciences (The National Academies Press, 2009)
The U.S. National Academies (NAS) and the Russian Academy of Sciences (RAS), building on a foundation of years of interacademy cooperation, conducted a joint project to identify U.S. and Russian views on what the international nuclear security environment will be in 2015, what challenges may arise from that environment, and what options the U.S. and Russia have in partnering to address those challenges. The project's discussions were developed and expanded upon during a two-day public workshop held at the International Atomic Energy Agency in November 2007. A key aspect of that partnership may be cooperation in third countries where both the U.S. and Russia can draw on their experiences over the last decade of non-proliferation cooperation. More broadly, the following issues analyzed over the course of this RAS-NAS project included: safety and security culture, materials protection, control and accounting (MPC&A) best practices, sustainability, nuclear forensics, public-private partnerships, and the expansion of nuclear energy.
Keywords: Conflict and Security Issues; Industry and Labor